2013
DOI: 10.1590/s0102-86502013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silibinin and ethanol on skeletal muscle ischemia-reperfusion injury

Abstract: PURPOSE:To investigate the potential beneficial effect of silibinin in ischemia-reperfusion injury (IRI) of skeletal muscle. METHODS: Under urethane anesthesia, four experimental groups were established in Balb/c mice: I) Sham-control, II) IRI (Tourniquet-induced) (2+1 h), III) IRI+ethanol (10%), and IV) IRI+silibinin (50 mg/kg/IP). The viability of muscle (left) was evaluated by the triphenyltetrazolium chloride dye method and calculated as the percentage of the contralateral control muscle (right). Malondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Second, skeletal muscle have longer endurance to IR injury than other susceptible organs. Drugs such as silibinin [24], iloprost [25], and dextran sulfate [26], which can attenuate the heart, renal, and brain IR injury have little effect in skeletal muscle injury. Finally, some drugs like hydrogen sulfide [2] and carbon monoxide [21], which are effective in physiologic dosage might be poisonous in moderate or high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Second, skeletal muscle have longer endurance to IR injury than other susceptible organs. Drugs such as silibinin [24], iloprost [25], and dextran sulfate [26], which can attenuate the heart, renal, and brain IR injury have little effect in skeletal muscle injury. Finally, some drugs like hydrogen sulfide [2] and carbon monoxide [21], which are effective in physiologic dosage might be poisonous in moderate or high doses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ischemic preconditioning [ 9 ], ischemic postconditioning [ 21 ], controlled reperfusion [ 22 ], hypothermia [ 23 ], light-emitting diode therapy [ 24 ] and some other physical therapies can relieve skeletal I/R injury [ 25 ]. In addition, several agents, such as dexamethasone [ 10 ], curcumin [ 26 ], salvianolic acid [ 8 ], silibinin [ 27 ], simvastatin [ 28 ], cyclosporine A [ 29 ], hydrogen-rich saline [ 30 ] and lipoxin A4 [ 4 ], have been shown to be effective in attenuating skeletal I/R injury. In cases of traumatic injuries in which I/R is not predictable and early intervention is desired, such strategies are not as relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a previous study performed in our laboratory, administration of 200 mg/kg silibinin had not been tolerated by the mice (i.e. almost all died probably due to lung edema), and the dose was reduced to an effective but not harmful level (50 mg/kg) 18 . Nevertheless, the probability of the highest dose of Legalon ® SIL being toxic is less than it simply being ineffective against cellular infarction in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, silymarin and silibinin have been found to exert beneficial effects in various IRI models established in different tissues, including the liver, the brain, the kidneys, the heart, and the intestine [9][10][11][12][13][14][15][16][17] . As there had been no prior investigations exploring the potential effect of silibinin on IRI of skeletal muscle, we previously made an attempt to investigate its effects in a rodent model 18 . Since silibinin is not water-soluble, we used ethanol to dissolve the substance.…”
mentioning
confidence: 99%